COVID‐19 and dengue infection in Bangladesh: A case of coinfection where hemoptysis as first presentation. Issue 1 (20th January 2022) - Amin, Mohammad Ashraful; Islam, Md Taufiqul; Khan, Ishtiakul Islam; Khan, Zahid Hasan; Qadri, Firdausi; Khan, Ashraful Islam
Abstract: Bangladesh recently faced large outbreaks of both COVID‐19 and dengue. We present a case of COVID‐19 and dengue coinfection in a patient who presented with hemoptysis. Our results demonstrate that COVID‐19 and dengue fever are both public health issues in Bangladesh and other dengue‐endemic nations and that they can coexist. Abstract : A case of COVID‐19 and dengue co‐infection in a patient who presented with hemoptysis.